2012
DOI: 10.1002/cbic.201100642
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept for Glycosyltransferase Inhibitors: Nonionic Mimics of the Nucleotide Donor of the Human Blood Group B Galactosyltransferase

Abstract: Glycosyltransferases play an important role in the formation of oligosaccharides and glycoconjugates. To find suitable and selective inhibitors for this class of enzymes is still challenging. Here, we describe a novel concept that allows the design of inhibitors based on the structure of the donor substrate binding pocket. As a first step we describe the design, synthesis and analysis of inhibitors of the human blood group B galactosyltransferase (GTB). This enzyme served as a model system to study the concept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…[77] In 2012, Meyer andc o-workers reported that pentitol-linkedu ric acid derivatives 104 and 105 (acyclic nucleoside analogues in which the nucleobase had also been replaced by a7 ,9-dihydro-1H-purine-2,6,8(3 H)-trione ring) showed similar bindinga ffinities to that of the natural substrate (UDPÀGal) to human blood group Bg lycosyltranferase (GTB) in the presence of Mg II . [78] 6-Chloronitrouracil (99)w as condensed with d-arabinitylamine (100)t op rovide compound 101,w hichw as transformed into compound 103 in two steps. Further intramolecular cyclization induced by sodium ethoxide provided compound 104.…”
Section: Modification At the Riboseunit And The Nucleobasementioning
confidence: 99%
“…[77] In 2012, Meyer andc o-workers reported that pentitol-linkedu ric acid derivatives 104 and 105 (acyclic nucleoside analogues in which the nucleobase had also been replaced by a7 ,9-dihydro-1H-purine-2,6,8(3 H)-trione ring) showed similar bindinga ffinities to that of the natural substrate (UDPÀGal) to human blood group Bg lycosyltranferase (GTB) in the presence of Mg II . [78] 6-Chloronitrouracil (99)w as condensed with d-arabinitylamine (100)t op rovide compound 101,w hichw as transformed into compound 103 in two steps. Further intramolecular cyclization induced by sodium ethoxide provided compound 104.…”
Section: Modification At the Riboseunit And The Nucleobasementioning
confidence: 99%
“…[28,31,[33][34][35][36] The main drawback of this approach is the anionic character of the inhibitors, which precludes their entry into cells due to repulsion by the anionic phospholipid bilayer. The preparation of neutral inhibitors of GTs [14,[37][38][39][40][41][42][43][44][45][46] is emerging as a promising strategy for in vivo biological applications. Because the diphosphate unit of the NDP sugars interacts with cations in metal-dependent GTs, any surrogate of this moiety should be capable of coordinating to the metal.…”
Section: Introductionmentioning
confidence: 99%
“…Non-competitive inhibitors have also been described that potentially alter the structure of the enzyme leading to inactive proteins ( 77 , 78 ). Modified nucleotide sugars are often recognized by GTs leading to transfer of unnatural sugars ( 143 ). Fluorescent groups modifying the base of the sugar-nucleotide can be useful as indicators of binding ( 144 ).…”
Section: Glycosyltransferase Inhibitorsmentioning
confidence: 99%